(untitled) (Education in the 21st Century, 2023)
Our article is dedicated to an in-depth examination and comparison of the higher education systems in the Republic of Armenia and Bulgaria. We will consider their distinctive characteristics within the realms of education, admission procedures, and other aspects related to governance, funding, and organizational structure. The article will also highlight optimal approaches and strategies for enhancing educational standards and achieving greater efficiency through various reform initiatives. The primary objective of this article is to meticulously investigate the higher education systems in Armenia and Bulgaria, conducting a comprehensive comparative analysis that unveils their commonalities and disparities. The findings from this study will be presented in a series of tables to facilitate a clear distinction between the unique features of these two nations’ higher education landscapes. Through our comparative analysis of higher education in Armenia and Bulgaria, we have reached the following conclusion: Both countries manage their higher education systems through state and intra-university levels, with oversight from central and local governmental bodies, albeit under differing nomenclature. Additionally, both nations are active participants in the Bologna process, though Bulgaria ratified the Bologna Declaration in 1999, whereas Armenia did so in 2005. Furthermore, both Armenia and Bulgaria have a mix of state and privately licensed universities. Armenian higher education institutions encompass universities, institutes, Academy of Science, and conservatory, whereas in Bulgaria, you will find universities, specialized higher schools, and colleges. Other distinctions within the higher education systems of these two countries include variations in admission procedures, structural arrangements, and grading systems. In conclusion, the examination and comparison of higher education management systems in Armenia and Bulgaria provide valuable insights that can be harnessed to enhance educational quality and productivity in either nation by adopting best practices from the other.